Opportunistic maintenance for offshore wind farms with multiple-component age-based preventive dispatch - Li, Mingxin; Jiang, Xiaoli; Negenborn, Rudy R. (Ocean engineering, 2021)
Operation & maintenance (O&M) costs account for a large portion of total life cycle cost for onshore wind energy, and the amount is estimated to be more for offshore wind energy. Developing a sound opportunistic maintenance strategy is a solution to reduce O&M costs and enhance wind energy's competitiveness. When the wind farm is located offshore, turbines are not only subject to degradation but also the impact from the harsh marine environment. However, the degradation is mainly regarded as the only cause of the failure in the existing opportunistic maintenance models for the offshore wind energy sector. At the same time, too frequent preventive dispatch of maintenance teams exists on some occasions. This paper proposes a maintenance strategy for offshore wind farms integrating three types of maintenance opportunities. In addition to the maintenance opportunities created by degradation failures and incidents, an age-based opportunity is introduced to improve the trigger of preventive dispatch. A numerical example is presented to illustrate the effectiveness of the proposed strategy. The comparative analysis shows 2.6% and 1.5% annual cost can be reduced respectively when compared with two traditional opportunistic maintenance strategies in the base scenario. [Display omitted] •A maintenance strategy is developed for offshore wind farms integrating three types of maintenance opportunities.•The degradation and environmental impact are simultaneously considered to describe the failure of the offshore wind turbine.•Preventive dispatch considering the states of multiple components is proposed to avoid frequent unnecessary maintenance.•Compared with two conventional strategies in the base scenario, the proposed strategy saves 2.6% and 1.5% cost respectively.